KONFLIK DAN KONSENSUS PEMERINTAHAN LOKAL : PEMILIHAN RUKUN TETANGGA (RT) 15 KELURAHAN KEBUN BUNGA KECAMATAN SUKARAMI DI KOTA PALEMBANG - M. Andry Mukmin; Reinhard Hutapea (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Rukun tetangga (RT) in sub district government system is the lowest or the unit of government holder who are directly connected to people. This means the last unit which is directly connected to people it, not sub district administration, district administration and so forth. RT plays the main role in accomplishing government functions, such as function of service, development, empowering, and regulation. That is why the more conducive the RT status is, the more conducive the government functions. Reversely, if the situation is not conducive, in this case, there is a conflict, then the function run will not be successfully accomplished. The conflict happened in the election of leader RT 15 Kebun Bunga sub district. The factors causing this conflict were the goal of this research. The data used were primer and secondary data. Those data then were analyzed using descriptive analysis which involved theories included concept of government, concept of conflict and consensus. From the analysis done, it was found out that factors causing the conflict included (a) the periode of incumbent - RT’s position had ended, (b) there was no good communication among RW, district chief and people (c) the seizure of economic sources in that area. It was suggested that (a) RW and district chief have a good communication to the people in that area, (b) all staff in sub district government take their parts maximally, and (c) the centre of economic area should be developed in that area.Keywords : Rukun tetangga, sub district, conflict, consensus